Pemberdayaan UMKM melalui Digitalisasi Pemasaran Produk olahan Kripik: Empowering SMEs through Digitalization of Marketing for Processed Chip Products - Ajeng Afriska Lailatul Fajriyah (AKSILAR: Akselerasi Luaran Pengabdian Masyarakat, 2023)
KKN Back to Village is a Real Work Lecture (KKN) program created by the University of Jember withthe aim that students can still carry out community service in their respective villages. This activity wascarried out in order to help the government to reduce the risk of the spread of COVID-19 which began toenter Indonesia since March 2020. One of the themes of KKN is related to the development of communityentrepreneurs affected by COVID-19. The target partners are entrepreneurs of various kinds of chips inthe village of girlfriend hug, Megaluh sub-district, Jombang district. This KKN activity is carried out tohelp entrepreneurs selling chips in developing and increasing sales targets for chips. The method usedin the implementation of this KKN is by sharing and practice. Sharing material with partners related tothings that are not widely known, namely product labels, product brands and product photos. Practicesare carried out by assisting partners in making product label designs, product brand designs, produceridentity designs, product production processes, product photos and product packaging and labeling. Theresults obtained from the implementation of KKN with entrepreneurial partners selling various chipsare the existence of products with a new look and also social media to sell online so that the sales targetis exceeded. Partners feel helped by the creation of product labels that are more attractive than before.The implementation of this KKN also produces brand names for partner products. Another resultobtained is that partners become aware of the important function of product testimonials.